Contributions to the taxonomy and faunistics of some arctic species of Spilogona Schnabl (Diptera: Muscidae) - Sorokina, Vera S.; Michelsen, Verner (Zootaxa, 2014)
New synonymies in the genus Spilogona Schnabl, 1911 are proposed: S. novaesibiriae (Frey, 1915) = S. obsoleta (Malloch, 1920), syn. nov.; S. trianguligera (Zetterstedt, 1838) = S. setinervis (Huckett, 1932), syn. nov. Spilogona trianguligera and S. tendipes (Malloch, 1920) are newly recorded from Greenland, and S. trianguligera also from W Siberia. The female of S. vikhrevi Sorokina, 2010 is described and the species in newly recorded from Wrangel Island (Far East Russia).